Nuclear envelope components in vascular mechanotransduction: emerging roles in vascular health and disease - Tung D. Nguyen; Michael A. Winek; Mihir K. Rao; Shaiva P. Dhyani; Monica Y. Lee (Nucleus)
The vascular network, uniquely sensitive to mechanical changes, translates biophysical forces into biochemical signals for vessel function. This process relies on the cell's architectural integrity, enabling uniform responses to physical stimuli. Recently, the nuclear envelope (NE) has emerged as a key regulator of vascular cell function. Studies implicate nucleoskeletal elements (e.g. nuclear lamina) and the linker of nucleoskeleton and cytoskeleton (LINC) complex in force transmission, emphasizing nucleo-cytoskeletal communication in mechanotransduction. The nuclear pore complex (NPC) and its component proteins (i.e. nucleoporins) also play roles in cardiovascular disease (CVD) progression. We herein summarize evidence on the roles of nuclear lamina proteins, LINC complex members, and nucleoporins in endothelial and vascular cell mechanotransduction. Numerous studies attribute NE components in cytoskeletal-related cellular behaviors to insinuate dysregulation of nucleocytoskeletal feedback and nucleocytoplasmic transport as a mechanism of endothelial and vascular dysfunction, and hence implications for aging and vascular pathophysiology.